Use of Causation Tests as a Systematic Approach to The Assessment of Causation in Claims of Medical Malpractice - Tümer, Ali Rıza; Yıldırım, Mahmut Şerif; Eskicioğlu, Emirhan; Akçan, Ramazan (The Bulletin of Legal Medicine, 2022)
When a claim of medical malpractice is encountered, it is an enormous problem to determine the “presence of causation”. The effect of other intervening factors on the resulting undesirable situation creates great difficulty in determining the causation. In these cases, it may be beneficial to apply causation tests prepared with a legal and philosophical perspective. In this paper, the most known and widely used of these tests, the “but for” test, as well as the lesser known and used “substantial factor” test and “INUS/NESS” tests were reviewed from the literature and their use in medical practice errors were explained with cases.
Keywords: clinical forensic medicine; causation; medical malpractice